The effect of Al and Nb contents, cooling rate and rolling condition on the microstructure and corrosion behaviour of HSLA steel - Qaban, Abdullah; Mohmed, Tasneem; M. M., Quazi; Naher, Sumsun (Elsevier, 2020)
The effect of the addition of aluminium and niobium, and processing conditions, including cooling rate and rolling condition, on the corrosion behaviour of HSLA steel in 10 wt% sulphuric acid environment has been investigated. The experimental procedures included electrochemical corrosion techniques using potentiodynamic and electrochemical impedance spectroscopy, as well as weight loss method. The microstructure was examined using optical and scanning electron microscopes in order to investigate the effect of the microstructural features on the corrosion behaviour. Surface films were evaluated by X-ray photoelectron spectroscopy (XPS) to identify the corrosion products formed on the surface. The results showed that increasing the Al content enhanced the corrosion resistance through obstructing pitting attack on the surface by the refinement of grain boundary carbides and the formation of a protective passive layer rich in carbide and oxide compounds. The combination of both Al and Nb promoted the corrosion resistance further, by enriching the passive layer with Nb and higher levels of carbide and oxide compounds, despite the presence of martensite and grain size refinement by NbCN. Increasing the cooling rate reduced the corrosion resistance due to the refinement of grain size, giving a higher density of grain boundaries that act as active sites, besides increasing the level of carbide distribution in the microstructure. Controlled rolling offered higher corrosion resistance than hot rolling, independent of the composition, because of the absence of martensite, the presence of low-angle boundary and the refinement of grain boundary carbides provided by controlled rolling.